The role of financial literacy, perceived risk, and technological advances in millennial generation investment decisions in the capital market - Kusuma, Putu Sri Arta Jaya; Mesacahyani, Ni Kadek (International research journal of management, IT and social sciences, 2023)
This study aims to determine the effect of financial literacy, risk perception and technological progress partially and simultaneously on the investment decisions of the millennial generation living in Denpasar city. The population in this study is the millennial generation from the city of Denpasar who have invested in the capital market. The sampling technique used non-probability sampling with a purposive sampling approach and the sample size was determined using the slovin formula so that 100 people were obtained as samples with the criteria set by the researcher. Empirical data was collected by distributing questionnaires online using the Google form. The data analysis technique in this study used the multiple linear regression analysis method with the help of the SPSS 26 software program. The results of this study indicate that financial literacy, risk perception, and technological advances have a significant positive effect on investment decisions in the capital market in the millennial generation in Denpasar city.